Islamic Family Law Perspective on Children Under Ages Who Work to Support Family (Study in Pasar Banggi Village, Rembang District, Central Java Regency) - Ibnu Aqil; Izzul Mutho`; Abdul Rozak; Muhammad Rizal Khoirul Umam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Many children under the age of 18 who have been actively involved in economic activities, become child laborers with the most dominant reason being economic pressure experienced by their parents or other factors. This study aims to determine the driving and underlying factors of children working as breadwinners for families in Pasar Banggi Village. As well as a review of Islamic family law on children as breadwinners for families in Pasar Banggi Village. This researcher uses qualitative methods, the data in this study were obtained from primary data and secondary data. Data collection techniques used are observation, interviews, and documentation. The results of this study indicate that the general description of working underage children due to the large number of them who work in Pasar Banggi Village as fishermen, farm laborers or other jobs is due to the most dominant economic factor, while other factors are environmental factors, parental factors, self-will factor, and habit factor. In terms of Islamic Family Law, the age limit for children to work is not directly explained in Article 98 of the Compilation of Islamic Law paragraph (1) the age limit for children who are able to stand alone or as adults is 21 years, as long as the child is not physically disabled. or mentally or have never been married. Child labor should be avoided considering the harm is greater than the benefit. In Surah Al-Baqarah verse 233 it is explained because providing a living is obligatory for parents.